Myeloperoxidase as inflammatory marker of periodontal disease: Experimental study in rats - Gomes, Dbora A. S.; Pires, Juliana R.; Zuza, Elizangela P.; Muscara, Marcelo N.; Herrera, Bruno S.; Spolidorio, Lus C.; Toledo, Benedicto E. C.; Spolidorio, Denise M. P. (Taylor & Francis, 2009)
Rationale: Previous studies have used myeloperoxidase (MPO) as an inflammatory marker to estimate the accumulation of neutrophils in inflamed regions. Objective: The aim of this experimental study was to quantify the levels of MPO related to experimental periodontal disease in rats. Methods: Periodontal disease was induced in a group of rats using placement of a ligature around molar teeth. A group of rats without ligature placement served as a control. Measurements were made on the 3rd, 7th, 15 th and 30th day from baseline. Gingival tissues were taken for quantification of MPO levels by ELISA. Results: The rats with induced periodontal disease showed statistically higher MPO levels (p < 0.05) when compared to control rats. A significant increase in the levels of MPO released on days 7 and 30 was observed, with higher levels in the group with induced periodontitis. Conclusion: The levels of MPO were found to be higher in rats with induced periodontal disease, confirming the hypothesis that MPO may serve as an inflammatory marker for periodontitis.
Keywords: Enzymes; Inflammation; Periodontal diseases; Peroxidase